IMPLEMENTASI PERENCANAAN STRATEGIS DALAM MENINGKATKAN MUTU PENDIDIK DI SMP AL FALAKHUSSA'ADAH DESA TANJUNG SERUPA KECAMATAN PAKUAN RATU KABUPATEN WAY KANAN TAHUN PELAJARAN 2023/2024 - M.YASIN (UNISAN JURNAL, 2024)
The A good strategic plan can support improving the quality of educators. Sometimes good planning doesn't always create good execution. The purpose of this research is to identify the effectiveness of strategic planning implemented at SMP Al Falakhussa’adah in improving the quality of educators. This study uses the type of field research used to answer research questions. The survey involved observations and interviews, as well as the collection of written documentation. Data is analyzed to present it in an effective manner and to verify its accuracy. After that, the writer uses source triangulation and method triangulation to ensure that the information is reliable. As a result of this research, the strategic plan of SMP Al Falakhussa’adah can be successfully implemented as follows. The principal performs several planning steps. For each respective task; identify and identify various laws, regulations, policies, and school teachers for improving the quality of educators. Realizing the vision, mission and values of the School. SWOT analysis. This activity is supported by the formed team. The implementation of the strategic plan at SMP Al Falakhussa’adah includes several actions, including preparing for the implementation of activities by holding meetings to determine the activities to be carried out and the main objectives of the activities. The principal chooses a training target at random. In practice, the principal ensures good communication between members. Principals and foundations work together to ensure that activities are carried out in schools. Strategic planning is evaluated periodically. Evaluation is carried out at the beginning of the year meeting, discussion of programs and activities to be carried out next year, preparation of action plans and schedule of the person in charge of activities.